Efficacy and safety of the enhanced monofocal intraocular lens in glaucoma of varying severity - Heesuk Kim; Junyeong Ahn; Minju Seo; Hyoung Won Bae; Chan Yun Kim; Wungrak Choi (Scientific Reports)
Abstract This study evaluates the safety and visual outcomes of enhanced monofocal intraocular lenses compared to standard monofocal intraocular lenses in patients with varying severities of glaucoma. Utilizing data from surgeries performed in 2021, the study involved patients aged 40 and older with visually significant cataracts and diagnosed glaucoma or glaucoma suspects. The findings indicate that both enhanced and standard monofocal lenses lead to significant improvements in best-corrected visual acuity, visual field index, mean deviation, and retinal nerve fiber layer thickness postoperatively. No significant differences were observed between the two groups in the extent of these improvements, suggesting that enhanced monofocal lenses may offer a viable alternative for patients with glaucoma, providing significant visual benefits and potentially better intermediate vision while preserving overall visual function.